2022
DOI: 10.1177/09567976221116816
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Programming of Behavior Problems via Second-by-Second Infant Emotion Dynamics

Abstract: Fetal adaptations to prenatal maternal stress may confer high risk for childhood behavior problems, potentially operating via dynamic fluctuations in infants’ emotions during mother–infant interactions. These fluctuations over time may give rise to behavior problems. Among a sample of 210 low-income mothers of Mexican origin and their 24-week-old infants, dynamic structural equation modeling was used to examine whether within-infant second-by-second emotion processes were predicted by maternal prenatal stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…And we are also unable to include the literature on how endogenous differences between children (in, for example, infant sensitivity) can mediate the relationship between caregiver psychopathology and child outcomes (Gueron-Sela et al, 2017;Somers et al, 2018). We are also not looking at prenatal influences (Somers & Luecken, 2022), such as direct hormonal influences.…”
Section: Part 4 -Studying Interpersonal Dynamics In Different Atypica...mentioning
confidence: 99%
“…And we are also unable to include the literature on how endogenous differences between children (in, for example, infant sensitivity) can mediate the relationship between caregiver psychopathology and child outcomes (Gueron-Sela et al, 2017;Somers et al, 2018). We are also not looking at prenatal influences (Somers & Luecken, 2022), such as direct hormonal influences.…”
Section: Part 4 -Studying Interpersonal Dynamics In Different Atypica...mentioning
confidence: 99%
“…Income-related stress and maternal mental health may alter the postnatal development of neurobiological systems underlying infant self-regulation through the shaping of the infant's stress physiology during pregnancy. This is often referred to as prenatal programming of infant neurobiological systems (Berens et al, 2017;Somers & Luecken, 2022). Additionally, low income is related to disruptions in pre-and postnatal maternal well-being (Knitzer et al, 2008) and parenting behaviors (Paulson et al, 2006), which in turn may account for the effects of low income on infant developmental outcomes.…”
mentioning
confidence: 99%
“…The prenatal period has been implicated as a sensitive window in development during which maternal stress can confer lasting impairments to children (Seckl & Holmes, 2007) through structural and functional changes in the fetus, referred to as prenatal programming (Somers & Luecken, 2022). Animal studies have consistently demonstrated that stress experienced in gestation alters offspring's organs, tissues, and systems and that these alterations result in lifelong observable changes to physiology, cognition, and behaviors (Weinstock, 2001).…”
mentioning
confidence: 99%